1998
DOI: 10.1074/jbc.273.6.3247
|View full text |Cite
|
Sign up to set email alerts
|

α Helix Content of G Protein α Subunit Is Decreased upon Activation by Receptor Mimetics

Abstract: To elucidate the mechanism whereby liganded receptor molecules enhance nucleotide exchange of GTPbinding regulatory proteins (G proteins), changes in the secondary structure of the recombinant G i1 ␣ subunit (G i1 ␣) upon binding with receptor mimetics, compound 48/80 and mastoparan, were analyzed by circular dichroism spectroscopy. Compound 48/80 enhanced the initial rate of GTP␥S binding to soluble G i1 ␣ 2.6-fold with an EC 50 of 30 g/ml. With the same EC 50 , the mimetic decreased the magnitude of elliptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…2 mM of each of four synthetic peptides and in vitro translated [ 35 S]G␣i3 were incubated with calnuc-Sepharose 4B in the presence of 15 mM Mg 2ϩ ͞2 mM Ca 2ϩ as described in Fig. 2 A, (30). Therefore, it seems reasonable to speculate that abolishing G␣i3's binding to calnuc by deletion of its C-terminal 12 amino acids may be caused by disruption of the ␣5 helix.…”
Section: Figmentioning
confidence: 99%
“…2 mM of each of four synthetic peptides and in vitro translated [ 35 S]G␣i3 were incubated with calnuc-Sepharose 4B in the presence of 15 mM Mg 2ϩ ͞2 mM Ca 2ϩ as described in Fig. 2 A, (30). Therefore, it seems reasonable to speculate that abolishing G␣i3's binding to calnuc by deletion of its C-terminal 12 amino acids may be caused by disruption of the ␣5 helix.…”
Section: Figmentioning
confidence: 99%
“…Follow-up studies corroborated the concept and demonstrated that numerous CADs act in a similar manner as mastoparan (Higashijima et al 1990;Mousli et al 1990b;Hagelüken et al 1995a;Breitweg-Lehmann et al 2002). Elegant mechanistic studies identified the interaction sites of mastoparan on Gproteins and revealed that mastoparan acts as a GPCR mimetic to promote GDP dissociation from G-protein α-subunits (Higashijima et al 1990;Weingarten et al 1990;Higashijima and Ross 1991;Tanaka et al 1998). Overall, the CAD studies with purified G-proteins corroborated the conclusions of studies obtained with intact cells.…”
mentioning
confidence: 96%
“…Between GST and G i1 , a PreScission Protease (GE Healthcare Biosciences) cleavage site (LEVLFQGP) was introduced. The expression plasmid for the K349P mutant of G i1 was prepared by ligating the DraI/SalI fragment of the pET24a(+)/K349P-G i vector (Tanaka et al, 1998), which has Lys349 replaced by Pro in His 10 -G i , into the DraI/SalI sites of pET24a(+)/GST-WT-G i1 , thus producing pET24a(+)/GST-K349P-G i1 . After confirmation of the sequences, the resultant expression plasmids were transformed into Escherichia coli BL21(DE3).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…NP_037277; gene ID 25686), was amplified using the pET24a(+)/ His 10 -G i vector (Tanaka et al, 1998) as the template, with forward primer 5 0 -ATGGGCTGCACACTGAGCGCTGAGGAC-3 0 and reverse primer 5 0 -CCGGTCGACTTAGAAGAGACCACAGTCTT-TTAG-3 0 . The amplified DNA fragment was blunted and digested with SalI.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
See 1 more Smart Citation